Relationship between lupus erythematosus and vitamin D - Rahmatova Feruza (Genius Journals, 2023)
The review presents literature data on the frequency of hypovitaminosis D in systemic lupus erythematosus (SLE), analyzes the association of clinical and laboratory parameters of the disease and vitamin D levels, and considers the possibilities of therapeutic use of its metabolites. The anti-resorptive, anti-inflammatory and immunomodulatory effects of vitamin D metabolites substantiate the expediency of their use in chronic inflammatory diseases in combination with traditional basic agents.
Keywords: vitamin D; systemic lupus erythematosus; hypovitaminosis D